Evaluation of [125I]α-Bungarotoxin Binding to α7 Nicotinic Acetylcholinergic Receptors in Hippocampus–Subiculum of Postmortem Human Alzheimer’s Disease Brain - Allyson Ngo; Fariha Karim; Oshini V. Keerthisinghe; Tram B. Danh; Christopher Liang; Jogeshwar Mukherjee (Receptors)
Background/Objectives: Alzheimer’s disease (AD) severely hinders cognitive function in the hippocampus (HP) and subiculum (SUB), impacting the expression of nicotinic acetylcholine receptors (nAChRs) such as the α7-subtype. To investigate α7 nAChRs as a potential PET imaging biomarker, we report the quantitative binding of [125I]α-Bungarotoxin ([125I]α-Bgtx) for binding to postmortem human AD (n = 29; 13 males, 16 females) HP compared to cognitively normal (CN) (n = 28; 13 male, 15 female) HP. Methods: For comparisons with common AD biomarkers, adjacent slices were anti-Aβ and anti-Tau immunostained for analysis using QuPath. Results: The [125I]α-Bgtx average SUB/HP ratio was 0.5 among the CN subjects, suggesting higher [125I]α-Bgtx binding in the HP gray matter regions. The AD subjects showed overall less binding than the CN subjects, with no statistical significance. A positive correlation was found in the [125I]α-Bgtx binding in the AD subjects as the age increased. The Braak stage comparisons of [125I]α-Bgtx were made with [18F]flotaza binding to Aβ plaques and [125I]IPPI binding to Tau. A positive correlation was found between [125I]α-Bgtx and [18F]flotaza and there was a negative correlation between [125I]α-Bgtx and [125I]IPPI, implicating intricate relationships between the different AD biomarkers. Conclusions: [125I]α-Bgtx shows complimentary potential as a α7 nAChR imaging agent but needs more preclinical assessments to confirm effectiveness for translational PET studies using α7 nAChR radioligands.